The development of English oral skills through the use of music with three year old children at "Mi Pequeño Mundo Day Care Center" - Ortiz Tirado, Ana Cristina (2011)
1. Theoretical framework. 2. Music and children. 3. Implementing songs and rhymes in the classroom. 4. Analysis of results. 5. Suggested songs and rhymes to be used in the class. 6. Conclusions and recommendations